The Logic of Collective Rating - Nax, Heinrich H. (Frontiers in Physics, 2016)
The introduction of participatory rating mechanisms on online sales platforms has had substantial impact on firms' sales and profits. In this note, we develop a dynamic model of consumer influences on ratings and of rating influences on consumers, focussing on standard 5-star mechanisms as implemented by many platforms. The key components of our social influence model are the consumer trust in the `wisdom of crowds' during the purchase phase and indirect reciprocity during the rating decision. Our model provides an overarching explanation for well-corroborated empirical regularities. We quantify the performance of the voluntary rating mechanism in terms of realized consumer surplus with the no-mechanism and full-information benchmarks, and identify how it could be improved.